Associations between physical exercise and social-emotional competence in primary school children - Pukui Wang; Xiang Gao; Xuyan Cui; Chenge Shi (Scientific Reports)
Abstract To investigate the impact of physical exercise on social-emotional competence in primary school children, and to examine the mediating role of peer attachment and the moderating role of gender. A stratified sampling method was employed to select students from grades 3 to 6 in six primary schools located in the eastern, central, and western regions of Hunan Province. The PARS-3, S-ECI, and Simplified IPPA were administered, resulting in the collection of 1180 valid questionnaires. (1) Correlation analyses revealed significant positive relationships between physical exercise and social-emotional competence, physical exercise and peer attachment, and peer attachment and social-emotional competence. (2) Peer attachment partially mediated the relationship between physical exercise and social-emotional competence in primary school children. (3) Gender differences were observed in the strength and direction of these relationships, with boys demonstrating stronger exercise-related benefits while girls exhibited greater developmental gains through enhanced peer relationships. Physical exercise is associated with the social-emotional competence of primary school children in a direct positive manner and can also be linked to this competence through the mediating of role peer attachment. Moreover, gender moderates the relationship between physical exercise and social-emotional competence, with physical exercise being more strongly associated with boys’ social-emotional competence than with girls’. However, as peer attachment increases, girls’ social-emotional competence tends to develop more favorably than boys’. These findings provide a theoretical basis for developing targeted physical exercise interventions to promote the social-emotional competence of primary school children.